Predictors and patterns of absenteeism among students with disabilities: implications for inclusive education - Whitley, Jess; Pegg, Shawn; Ozturk, Mina (Frontiers in Education, 2026)
IntroductionInclusive education requires that students with disabilities are present and supported to participate meaningfully, yet many continue to experience limited access to schooling. School absenteeism—including partial-day schedules and informal exclusions—remains an overlooked barrier to inclusive education.MethodsParents/caregivers of 540 Ontario students with disabilities completed a survey about attendance patterns, school belonging, and reasons for absences. Analyses included descriptive statistics, linear regression, and content analysis of open-ended responses.ResultsTwenty-one percent of students attended school on a part-time or modified schedule, most commonly 2–3 h per day, and about 40% met criteria for chronic absenteeism. The most frequent reasons for absences included emotionally based school avoidance, parents keeping children home due to unmet needs, and school-initiated exclusion tied to behavior or insufficient staffing. Students reporting lower school belonging, who attended school on a part-time or modified schedule, and from families with lower income had significantly higher levels of absenteeism.DiscussionHigh levels of absenteeism and part-time attendance represent systemic forms of exclusion that undermine participation and achievement in inclusive education. Findings point to the critical role of school belonging, adequate supports, and socioeconomic context in promoting regular attendance and advancing inclusive education.